2015
DOI: 10.1002/biof.1225
|View full text |Cite
|
Sign up to set email alerts
|

Unique features of human cathelicidinLL‐37

Abstract: Cathelicidins are antimicrobial peptides produced by humans and animals in response to various pathogenic microbes. This review intends to provide a brief overview of the expression, structure, properties and function of human cathelicidin LL-37 which may be a therapeutic agent against a variety of bacterial and viral diseases, cancers, and hard-to-heal wounds. Cathelicidins act as a primary defense against bacteria and other pathogens in the case of inflammation. They are able to kill bacteria and fungi, inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 210 publications
1
90
0
Order By: Relevance
“…Thus, as an alternative member of the cathelin family, LL-37 has been highly expressed in human psoriatic keratinocytes [47]. As the human homolog to PR-39, LL-37 peptides not only possess a broad antibacterial spectrum, but also have angiogenesis and anti-apoptotic effects [48,49]. Vázquez-Sánchez et al [50] reported that the anti-apoptotic effect of LL-37 is also mediated through the up-regulation of c-IAP-2 via the caspase-3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as an alternative member of the cathelin family, LL-37 has been highly expressed in human psoriatic keratinocytes [47]. As the human homolog to PR-39, LL-37 peptides not only possess a broad antibacterial spectrum, but also have angiogenesis and anti-apoptotic effects [48,49]. Vázquez-Sánchez et al [50] reported that the anti-apoptotic effect of LL-37 is also mediated through the up-regulation of c-IAP-2 via the caspase-3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial peptide cathelicidin is induced by the active form of vitamin D [1,25(OH) 2 Cathelicidin has been shown to have direct antibacterial, antifungal, antiviral, and immunoregulatory properties when added to infected cells and cultures in vitro (6). It kills bacteria by disrupting bacterial membranes and blocks viral entry by interacting with viral proteins, suppressing viral entry and/or replication (6).…”
Section: Vitamin D and Cathelicidinmentioning
confidence: 99%
“…It kills bacteria by disrupting bacterial membranes and blocks viral entry by interacting with viral proteins, suppressing viral entry and/or replication (6). Cathelicidin can both inhibit the growth of and increase the virulence of P. aeruginosa via mutation, resulting in chronic infection (7).…”
Section: Vitamin D and Cathelicidinmentioning
confidence: 99%
See 2 more Smart Citations